The mechanisms underlying the immune control of Zika virus infection at the maternal-fetal interface - Espino, Ana; Gouilly, Jordi; Chen, Qian; Colin, Philippe; Guerby, Paul; Izopet, Jacques; Amara, Ali; Tabiasco, Julie; Al-Daccak, Reem; El Costa, Hicham; Jabrane-Ferrat, Nabila (Frontiers in Immunology, 2022)
Unlike other Flaviviruses, Zika virus (ZIKV) infection during the first trimester of pregnancy causes severe pregnancy outcomes including the devastating microcephaly and diseases associated with placental dysfunctions. We have previously reported that the maternal decidua basalis, the major maternal-fetal interface, serves as a replication platform enabling virus amplification before dissemination to the fetal compartment. However, the rate of congenital infection is quite low, suggesting the presence of a natural barrier against viral infection. Using primary cells from first-trimester pregnancy samples, we investigated in this study how maternal decidua can interfere with ZIKV infection. Our study reveals that whether through their interactions with dNK cells, the main immune cell population of the first-trimester decidua, or their production of proinflammatory cytokines, decidual stromal cells (DSCs) are the main regulators of ZIKV infection during pregnancy. We also validate the functional role of AXL as a crucial receptor for ZIKV entry in DSCs and demonstrate that targeted inhibition of ligand-receptor interaction at the early stage of the infection is effective in drastically reducing virus pathogenesis at the maternal-fetal interface. Collectively, our results provide insights into the mechanisms through which ZIKV infection and spreading can be limited. The strategy of circumventing viral entry at the maternal-fetus interface limits virus dissemination to fetal tissues, thereby preventing congenital abnormalities.